Arabic Language Learning Program in Non-Formal Classroom and Factors That Influence Its Completeness (Case Study in One of the Housing Complexes in Karawang) - Muhammad Sutrisno; Tubagus Kesa Purwasandy; Mulhendra Mulhendra (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the factors that influence the learning achievement of participants in a non-formal Arabic language learning program and identify possible solutions to overcome these obstacles. This study used a qualitative approach with data collection techniques such as observation, interviews, and reflective journals. The results showed variations in learning achievement; some respondents had never completed a program, while others had successfully completed certain programs such as Muyassar volume 1, Ilmu Shorof, and BISA. Inhibiting factors were divided into two categories: internal and external. Internal factors included low learning motivation and difficulty understanding the material, while external factors included workloads, schedule conflicts, health conditions, family responsibilities, and minimal social support. Some solutions proposed by respondents included time flexibility, improving teaching quality, social support, utilizing technology, more effective learning methods, fostering motivation, and establishing learning priorities. These findings indicate that implementing non-formal Arabic language learning requires a holistic, adaptive, and integrative approach to enable students to achieve optimal program completion.